Biogeography and Biodiversity of the Intertidal Barnacle Tetraclita Species in the Gulf of Thailand and Andaman Sea – Influences of Oceanographic Currents and Pleistocene Glaciations - Chan, Benny K. K.; Tsao, Yao-Feng; Wangkulangkul, Kringpaka; Amjud, Kittipong; Sukparangsi, Woranop (Frontiers in Marine Science, 2022)
The present study investigated the phylogeography of the intertidal barnacle Tetraclita in the Gulf of Thailand ecoregion (Sunda Shelf Province in the Pacific) and the Andaman Sea Coral Coast ecoregion (Andaman Province in the Indian Ocean) in Thailand’s waters. Tetraclita species were identified by a combined morphological and molecular approach using mitochondrial gene fragments (CO1 and 12S rRNA). Tetraclita singaporensis is a major occupiers on the Andaman coast but is sparse in the western Gulf of Thailand. Tetraclita squamosa inhabits almost all of our collection sites in the Gulf of Thailand but has a very low abundance in the Andaman Sea. Tetraclita kuroshioensis has two genetically distinct populations, one in the Andaman Sea and the other in the West Pacific region. S-DIVA analysis showed that the most recent common ancestor (MRCA) of T. kuroshioensis was distributed in both the Andaman Sea and West Pacific region, with a relative probability of 63%; the analysis further identified two molecular subclades, one on each side of the Sunda Shelf by vicariance about 0.53 million years ago, far before the Last Glacial Maximum (LGM). The MRCA of T. squamosa was based in the West Pacific region (relative probability: 90%), and dispersed into the Andaman Sea after the LGM. The MRCA of T. singaporensis was in the Andaman Sea (relative probability: 89.5%) and dispersed into the Gulf of Thailand via monsoonal currents through the Malacca Strait after the LGM. Presently, T. singaporensis is absent from the West Pacific region, further supporting its origin in the Andaman Sea. The distribution of intertidal barnacles in the Sunda Shelf and Andaman provinces is a result of the interplay between geological events and present day oceanographic currents.